Efficacy and safety of single-pill amlodipine/losartan versus losartan in patients with inadequately controlled hypertension after losartan treatment: a multicenter, double-blind, randomized phase III clinical trial - Zhang, Shuyang; Li, Ying; Xu, Xin; Xu, Rui; Zhang, Linchao; Wan, Xiaoqun; Yao, Zhuhua; Sun, Yuemin; Liu, Yong; Bin, Jianping; Wang, Zhen; Li, Shuren; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objective: Single-pill amlodipine besylate (AML) plus losartan (LOS) has been used to treat inadequately controlled hypertension after antihypertensive monotherapy; however, relevant data in China are limited. This study aimed to compare the efficacy and safety of single-pill AML/LOS and LOS alone in Chinese patients with inadequately controlled hypertension after LOS treatment. Methods: In this multicenter, double-blind, randomized, controlled phase III clinical trial, patients with inadequately controlled hypertension after 4 weeks of LOS treatment were randomized to receive daily single-pill AML/LOS (5/100 mg, AML/LOS group, N = 154) or LOS (100 mg, LOS group, N = 153) tablets for 8 weeks. At weeks 4 and 8 of treatment, sitting diastolic and systolic blood pressure (sitDBP and sitSBP, respectively) and the BP target achievement rate were assessed. Results: At week 8, the sitDBP change from baseline was greater in the AML/LOS group than in the LOS group (-8.84 ± 6.86 vs. -2.65 ± 7.62 mmHg, P < 0.001). In addition, the AML/LOS group also showed greater sitDBP change from baseline to week 4 (-8.77 ± 6.60 vs. -2.99 ± 7.05 mmHg) and sitSBP change from baseline to week 4 (-12.54 ± 11.65 vs. -2.36 ± 10.33 mmHg) and 8 (-13.93 ± 10.90 vs. -2.38 ± 12.71 mmHg) (all P < 0.001). Moreover, the BP target achievement rates at weeks 4 (57.1% vs. 25.3%, P < 0.001) and 8 (58.4% vs. 28.1%, P < 0.001) were higher in the AML/LOS group than those in the LOS group. Both treatments were safe and tolerable. Conclusion: Single-pill AML/LOS is superior to LOS monotherapy for controlling BP and is safe and well tolerated in Chinese patients with inadequately controlled hypertension after LOS treatment.